SOSIALISASI PENINGKATAN KUALITAS DAN PRODUKTIVITAS UBI JALAR MELALUI PENERAPAN SYSTEM PENANGANAN PANEN - M. Azizi; Syaifullah Rahim; Trisday Yiin Parari; Muhammad Amran (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity was carried out in theArfak Mountains region of West Papua, with the aim of improving the qualityand productivity of sweet potatoes through the implementation of an appropriate harvest handling system. The main problem faced by farmers is the high rate of physical damage to the tubers due to inappropriate harvesting methods, such asthe use of unsuitable tools and methods of lifting the tubers that causeinjuries. This activity was carried out by the outreach team using methods oflectures, field demonstrations, and interactive discussions. The material providedcovered determining the ideal harvest time, safe digging and liftingtechniques, as well as the sorting and grading process for the harvest. The results of the activityshowed an increase in farmers' knowledge and skills inharvest handling, thereby reducing the level of tuber damage and improving the quality ofthe yield. This activity was also followed up with continuous guidance and consultation to ensure the application of the techniques that had been learned. Overall, this program succeeded in increasing farmers' awareness of the importance ofproper harvest handling in maintaining the quality and selling value of sweet potatoes in theArfak Mountains..